Experimental Study on Seepage Characteristics of Jurassic Weakly Cemented Sandstone under Water-Rock Interaction - Qin Liu; Yajun Sun; Jian Li (Geofluids)
As unconventional water-bearing rocks, the hydraulic conductivity of weakly cemented sandstones can increase by several orders of magnitude during drainages or pumping tests, posing great challenges to water prevention and control of coal mines in northwestern China. In this study, seepage experiments on Jurassic weakly cemented sandstones were performed and the hydraulic conductivity during the seepage process was analyzed. Combined with laboratory test and theoretical analysis methods, the relation between the permeability and micropore structures was studied, and the permeability evolution mechanism of the weakly cemented sandstones was eventually clarified. According to the experimental results, the seepage process can be divided into the saturated seepage stage, the stable seepage stage, and the seepage mutation stage. The hydraulic conductivity increases as the porosity and the mercury extrusion rate increase, but there is no obvious correlation between them that can be identified. In contrast, there is a linear positive correlation between the hydraulic conductivity and the average pore-throat radius. The variation trend of the pore-throat ratio can be used as the main reference indicator for judging whether the seepage mutation occurs in weakly cemented sandstone. Based on the correlation analysis of micropore structures and the hydraulic conductivity, a seepage model of straight capillary was constructed and the theoretical permeability equations of stable seepage stage and seepage mutation stage were proposed. It is concluded that the specific permeability of weakly cemented sandstones is directly proportional to porosity and the square of the average pore-throat radius. A theoretical equation to calculate the specific permeability during the latter two stages was also presented in this paper. Theoretical calculation results are roughly consistent with actual values obtained in the experiments.